Access to Chiral Tertiary α-Hydroxy-β-Ynyl Esters via One-Pot Addition and Kinetic Resolution - Chen, Hong-Bin; Lai, Wen-Han; Zhao, Yan; Qin, Dan-Dan; Ruan, Yuan-Ping; Zhou, Zhao-Hui (Synlett, 2014)
Chiral amino alcohol promoted one-pot addition of zinc alkynylides to α-keto esters and kinetic resolution of the resulting tertiary propargylic alcohols was developed. The reaction provided us an alternative approach to access optically active tertiary α-hydroxy-β-ynyl esters with enantiomeric excesses up to 98%.
Keywords: alkynylation; propargylic alcohols; tertiary α-hydroxyl esters; kinetic resolution; amino alcohol